EFFECT OF ALBIZIA LEBBECK PODS USED AS SOIL AMENDMENT ON THE GROWTH OF SOLANUM AETHIOPICUM (GARDEN EGGS) - Damian, Tom-Dery; Abdul-Rafiq, Mohammed; Asante, William J.; Issifu, Hamza; Ochire-Boadu, Kwame (UDS International Journal of Development, 2016)
In the array to assess the suitability of using amendments from nitrogen fixing trees in agroforestry, the response of Solanum aethiopicum to Albizia lebbeck pod amendment was investigated in a plant house experiment at the University for Development Studies-Nyankpala campus. The objective of this study was to determine the effect of different levels of A. lebbeck pods used as soil amendment on the growth of S. aethiopicum. Different amounts of the powdery form of A. lebbeck pods were mixed with 6kg of well-drained soil in four treatment levels; T0 (control- 6kg soil with no amendment), T1 (0.130kg pod amendment in 6kg soil), T2 (0.195kg pod amendment in 6kg soil) and T3 (0.260kg pod amendment in 6kg soil) which were put in 1.132 m3 plastic buckets and arranged in a randomized complete block design. Albizia lebbeck pod amendment applied at T1, T2 and T3 significantly promoted certain growth parameters relative to T0 (control). However, exact effects depended on the particular growth parameter measured. For example T2 and T3 significantly increased number of leaves and leaf area index, but not plant height. Effects of T2 and T3 on mean leaf number were similar but different from T1. Mean heights of plants grown in T1 and T3 were higher (although not statistically significant) than T2 and T0. Although certain growth parameters were more affected than others, application of A. lebbeck pod amendment generally improved growth performance of Solanum aethiopicum, making it suitable for use as soil amendment for the cultivation of garden eggs. Keywords: Soil amendment, Albizia lebbeck, Solanum aethiopicum, plant growth and soil amendmentÂ 